2019
DOI: 10.2478/hukin-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Review and Match Analysis of Rugby World Cups Finals

Abstract: The aim of this study was to describe the game related statistics and match analysis of rugby world cups finals from 1987 to 2015. Video recordings of all (n = 8 matches) rugby world cup finals were used for the purpose of this study. Games were analysed using the video analysis software (Sports code V8.9, Sportstec, Australia) and supplementary data were collected from the official reports published by the International Rugby Board and from webpages of Rugby World Cups. Magnitude of differences between the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Studies in rugby league have reported matches against stronger opposition have small-to-moderate increases in HSR distances [ 67 ]. However, other studies in rugby have demonstrated that defensive play has a greater impact on world cup finals compared to attacking play [ 68 ]. This may explain the decrease in HSR activity during finals as increases in defensive play could lead to more stoppages and congestion which has been previously shown in AF to reduce player activity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rugby league have reported matches against stronger opposition have small-to-moderate increases in HSR distances [ 67 ]. However, other studies in rugby have demonstrated that defensive play has a greater impact on world cup finals compared to attacking play [ 68 ]. This may explain the decrease in HSR activity during finals as increases in defensive play could lead to more stoppages and congestion which has been previously shown in AF to reduce player activity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 Numerous studies have examined PIs while comparing winning and losing teams across prestigious tournaments like Rugby World Cups and Six Nations championships. In this context, Vaz et al 8 emphasised the multifaceted nature of rugby and underscored the significant impact of contact interactions, such as scrums (winning = 10.63; losing 8.43), rucks (winning = 90.0; losing = 64.0) and tackles attempted (winning = 84.63; losing = 82.57), on performance outcomes. For instance, Hughes et al 9 conducted a study analysing PIs during the knockout stages of the 2015 Rugby World Cup for men and the 2014 Rugby World Cup for women.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these, players should secure the holding of balls in a proper position that allows them to manipulate the balls in passing and catching more accurately. It is generally believed that good handling skills could contribute to a decrease in turnover, hence an increase in winning probability (Ross, 2015;Vaz, 2019). Rugby is an outdoor game that is likely to be played under various weather conditions in terms of temperature, humidity and wind, which may affect the rugby balls' frictional behaviour and travelling speed, as well as players' performances of tasks in games.…”
Section: Introductionmentioning
confidence: 99%